Genetic diversity of Borrelia burgdorferi sensu lato isolates obtained from Ixodes ricinus ticks collected in Slovakia - Gern, Lise; Hu, Chang Min; Kocianova, Elena; Vyrostekova, Vanda; Rehacek, J. (My University, 1999)
In Europe, Borrelia burgdorferi sensu lato is diverse, including B.burgdorferi s.s., B.garinii, B.afzelii, B.valaisiana and B.lusitaniae. In this study, we focused on the distribution of the different B.burgdorferi species among Ixodes ricinus adult ticks collected in an endemic area within Slovakia. We compared results of prevalence of B.burgdorferi infection in ticks obtained by immunofluorescence (IF) and by isolation. Isolates were characterized by restriction fragment length polymorphism (RFLP) of the rrf-rrl intergenic spacer genes using MseI. Using immunofluorescence we observed that 56/114 (49%) ticks were infected by B.burgdorferi s.l. Males were found to be more often infected (32/57, 56%) than females (24/57, 42%) but the difference was not significant (p=0.1895). From the same 114 ticks a total of 37 isolates were obtained: 19 from males (33%) and 18 from females (32%). The RFLP identification revealed 25 B.afzelii (68%), 5 B.garinii (14%), 5 B.valaisiana (14%) and 2 B.lusitaniae (5%). The infection in ticks was more often detected by IF than by isolation (p=0.0153) and isolation success was higher when the infection degree in ticks was high (p=0.0397). The infection prevalence observed in this area is among the highest observed in Europe.
Keywords: Borrelia burgdorferi s.l.; Immunofluorescence; Isolation; Ixodes ricinus